Poor Glycemic Control: Prevalence and Risk Factors Among Patients with Type 2 Diabetes Mellitus in Northeast State of Peninsular Malaysia - Awang, Hafizuddin; Ja’afar, Siti Mariam; Wan Ishak, Nurul Adhiyah; YusofZainal, Muhamad; Mohamed Aminuddin, Abdul Mukmin; Dollah, Zawiyah (International Journal of Human and Health Sciences (IJHHS), 2020)
Background: Poor glycemic control remains an on-going public health concern worldwide. With the increasing prevalence of diabetes mellitus in Malaysia, good control of blood glucose level is paramount to avert life-long complications of diabetes mellitus. Hence, this study aimed to determine the prevalence of poor glycemic control and its associated factors to assist clinicians in achieving good glycemic control among diabetic patients. Materials and Methods: A comparative cross-sectional study between groups of good glycemic control and poor glycemic control patients was conducted among type 2 diabetes mellitus (T2DM) patients who fulfilled study criteria in Pasir Puteh district, Kelantan, a northeast state of Peninsular Malaysia. Eligible samples registered in the National Diabetes Registry from 1st January 2019 until 31st December 2019 were recruited into the study. Descriptive statistics, simple and multiple logistic regressions were used for data analysis. Results: The prevalence of patients with poor glycemic control in Pasir Puteh district was 79.6%% (95% CI: 0.78, 0.81). Multivariable analysis using multiple logistic regression revealed age, duration of diabetes, cigarette smoking, presence of hypertension and presence of dyslipidaemia were the significant factors associated with poor glycemic control among T2DM patients in Pasir Puteh district with an adjusted odds ratio (AOR) of 0.93 (95%CI:0.91, 0.94); p<0.001), AOR 1.19 (95%CI:1.14, 1.25; p<0.001), AOR 2.75 (95%CI:1.52, 4.97; p=0.001), AOR 2.19 (95%CI:1.32, 3.62; p=0.002) and AOR 2.16 (95%CI:1.45, 3.21; p<0.001) respectively. Conclusion: This study provided important criteria for clinicians to improve management of diabetes mellitus and optimize glycemic control based on the pinpointed significant risk factors. International Journal of Human and Health Sciences Vol. 04 No. 03 July’20 Page : 206-214